A Comparison of Cognitive Restructuring and Thought Listing for Excessive Acquiring in Hoarding Disorder - Levy, Hannah C. (Cognit Ther Res, 2019)
Excessive acquiring is a common symptom of hoarding disorder (HD). Little is known about subjective distress associated with acquiring in HD. The present study examined acquiring- related distress and reactions to cognitive restructuring (CR) in 92 individuals with HD and 66 community control (CC) participants. All participants identified an item of interest at a high-risk acquiring location and then decided whether or not to acquire the item. HD participants completed the acquiring task while receiving a CR-based intervention or a thought-listing (TL) control condition. Results showed that HD participants reported more severe distress and greater urges to acquire the item of interest than did CC participants. Nevertheless, subjective distress decreased in both groups following the acquiring task. There were no differences in acquiring- related distress between the CR and TL conditions. The findings indicate that subjective distress may decrease after relatively short periods of time in individuals with HD, but that a single session of CR may not alleviate acquiring-related distress in HD participants.